POTENTIAL OF PALM KERNEL SHELL (PKS) AS CARBON SUPPORT TO BIMETALLIC CATALYST (Cu-Ce) IN A HYDROCARBON SELECTIVE CATALYTIC REDUCTION (HC-SCR) OF NOx - Melvina, Tan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Generally, a lot of research has centered to developed carbon support catalyst in a Selective Catalytic Reduction technology to enhance catalytic activity at low temperature. However, the application of palm kernel shell as carbon supported catalyst for SCR has not being broadly studied. Furthermore, the common applications of ammonia in SCR are considered unsuitable and difficult to handle. Therefore, this study was to investigate the potential of palm kernel shell as carbon support to bimetallic catalyst (Cu-Ce) in Hydrocarbon Selective Catalytic Reduction (HC-SCR) to reduce NOx from diesel engine. Several analyses were conducted to study the characterization and activity of catalyst that were prepared by using deposition-precipitation method. Characterization analysis involved Fourier-Transform Infrared Spectroscopy (FTIR), Brunauer–Emmett–Teller (BET), X-Ray Fluorescence (XRF) and Hydrogen Temperature-Programmed Reduction method (H2-TPR). In addition, catalytic activity was performed to determine NOx reduction at various temperatures, mainly at 140°C, 180°C, 220°C, 260°C and 300°C. From the BET analysis, the best catalyst found was copper supported on palm kernel shell (Cu/PKS) while the lowest surface area and pore volume was shown by cerium loading (Ce/PKS). However, XRF result showed that metal loading of cerium supported on palm kernel shell (PKS) was the highest (91.2%) as compared to other types of metal catalyst studied. In terms of catalytic activity, raw PKS shows the highest NOx reduction by 61% at 220°C. Thus, PKS is a good support to metal catalyst Selective Catalytic Reduction (SCR) of NOx but excess addition of metal catalyst either cerium or copper inhibit the performance of bimetallic catalyst on activated carbon as overall.